2005
DOI: 10.2189/asqu.2005.50.3.367
|View full text |Cite
|
Sign up to set email alerts
|

Affect and Creativity at Work

Abstract: This study explored how affect relates to creativity at work. Using both quantitative and qualitative longitudinal data from the daily diaries of 222 employees in seven companies, we examined the nature, form, and temporal dynamics of the affect-creativity relationship. The results indicate that positive affect relates positively to creativity in organizations and that the relationship is a simple linear one. Time-lagged analyses identify positive affect as an antecedent of creative thought, with incubation pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

43
1,121
2
28

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,665 publications
(1,248 citation statements)
references
References 100 publications
43
1,121
2
28
Order By: Relevance
“…As indicated affection and emotions (both positive and negative) have been shown to be linked with multiple cognitive, interpersonal outcome, and physiological activities (Fredrickson, 2001). Empirical studies in the field of creativity suggest that emotions (both positive and negative mood) have a significant role to enhance creativity at work too (George and Zhou, 2002;Amabile et al, 2005;Zhou and George, 2001). The broaden-and-build theory (Fredrickson, 1998) describes the meaning of a subset of positive emotions, including joy, love, happiness, and well-being.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As indicated affection and emotions (both positive and negative) have been shown to be linked with multiple cognitive, interpersonal outcome, and physiological activities (Fredrickson, 2001). Empirical studies in the field of creativity suggest that emotions (both positive and negative mood) have a significant role to enhance creativity at work too (George and Zhou, 2002;Amabile et al, 2005;Zhou and George, 2001). The broaden-and-build theory (Fredrickson, 1998) describes the meaning of a subset of positive emotions, including joy, love, happiness, and well-being.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies indicated that there is a significant relationship between individual well-begin and creativity (Shalley et al, 2000). As indicated by prior studies positive mood plays a significant role in relationship between work environment and employees' health, safety, productivity and creativity (Fredrickson and Branigan, 2005;Harter et al, 2003;Shipton et al, 2006;Waugh and Fredrickson, 2006;Amabile et al, 2005). Previous studies also have supported the concept of positive emotion to enhance satisfaction, motivation and productivity at work (Martin, 2005).…”
Section: Introductionmentioning
confidence: 86%
See 2 more Smart Citations
“…Consistent with this view, individuals indeed perform better when they experience PA (Amabile, Barsade, Mueller, & Staw, 2005;Isen, Daubman, & Nowicki, 1987;Wright, Cropanzano, & Meyer, 2004). These beneficial effects of PA are likely to be more apparent for complex cognitive tasks than for well-structured procedural tasks (Gillet et al, 2013;McGraw, 1978).…”
Section: Summary Of Findingsmentioning
confidence: 87%